Pengembangan Pembelajaran Inovatif Pendidikan Agama Kristen Berdasarkan Efesus 2:10 untuk Meningkatkan Kompetensi Profesional Guru di Sekolah Kristen Kota Palu, Sulawesi Tengah di Era Digital - Meike Irmawati Tompira; Tonny Andrian Stefanus; Maria Titik Windarti (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
Christian Religious Education (PAK) in the digital era faces great challenges as well as opportunities to develop through learning innovation. With a theological foundation such as Ephesians 2:10, this education does not only aim to develop cognitive aspects, but also to shape character oriented towards personal and spiritual transformation. PAK teachers are required to be inspirers who integrate faith values with innovative learning approaches, such as the utilisation of digital technology, the development of student-based learning models, and the application of creative methods, such as gamification and blended learning.However, this digital transformation is not without obstacles. In Palu City, geographical challenges, technological limitations, and diverse student backgrounds are important issues that need to be addressed. By implementing strategies such as teacher training, collaboration with churches, and contextualised curriculum development, PAK can adapt and be relevant to the times. This research uses a literature review to explore the concept and implementation of innovations in PAK, including improving teachers' skills in technology, learning management, and communication. The results show that a constructivism-based approach, which emphasises hands-on experience and active learning, can improve learning effectiveness. The synergy between technology, faith and local context is the key to the success of Christian education that is able to produce a generation with character and competence to face the digital era..